The Role of Brand Image in Mediating the Influence of Digital Marketing and Customer Relationship Marketing on Tourist Decisions - Rokhmad Budiyono; Arini Novandalina (Journal of Economic Education, 2023)
This research aims to analyze the impact of digital marketing and customer relationship marketing on the formation of brand image at the Old City of Semarang tourist attraction, identify the impact of brand image on the decisions of tourists visiting the Old City of Semarang, and assess the influence of digital marketing on tourists' decisions at tourist attractions. Semarang Old City, through the mediation of brand image. Researchers used three types of variables in this research. Validity testing was carried out using SPSS software, and the instrument was considered valid if the correlation value (r) ≥ 0.30; instruments with correlation values ​​below 0.30 are considered invalid, and these variables can be eliminated. Apart from that, the reliability value is measured by a Cronbach alpha value above 0.6. The research results show that digital marketing has a positive and significant impact on brand image. However, digital marketing does not have a positive impact on tourists' decisions. Brand image has a positive and significant influence on tourists' decisions. Apart from that, customer relationship marketing influences brand image, and customer relationships also influence tourists' decisions. However, indirectly, digital marketing does not have a positive impact on tourists' decisions through brand image, because brand image is unable to mediate the relationship between digital marketing and tourists' decisions.